MORINGA OLEIFERA - A NEVER DIE TREE: AN OVERVIEW - Swati; Kaur Virk, Amanpreet; Kumari, Chandresh; Ali, Aaliya; Garg, Prakrati; Thakur, Pratibha; Attri, Chandrika; Kulshrestha, Saurabh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Moringa oleifera (MO) is mostly inhabiting in the tropical and subtropical regions of the world. It is notable for its therapeutic and nutritious qualities on the grounds that each piece of this plant can be exploited for restorative and sustenance purposes. The restorative and healthful qualities are because of the nearness of certain essential and optional metabolites contained by the plant. The phytochemicals screening uncovered the occurrence of auxiliary metabolites. These bioactive mixes can be utilized as a part of curing numerous ailments. MO is a versatile plant whose seeds comprise an excellent consumable oil (up to 40% by weight) and water-solvent protein that acts viable coagulants for water and wastewater treatment. The fruitful utilization of shelled MO Lam. seeds as a biosorbent presents a more affordable ecologically inviting technique for the expulsion of different irresistible metals from contaminated watery media. Aside from turbidity expulsion, MO, additionally, has antibacterial properties. The aim of this review is to present a complete analysis of the traditional uses and pharmacological properties of MO. Furthermore, this review is to update wide numbers of phytochemical constituents which have been isolated from the plant, and these constituents possess several medicinal properties.